Limb force generation as a limiting factor for maximum-effort acceleration performance - Luo, G.; Stefanyshyn, D. J. (Sports Performance, 2015)
Sprint acceleration is important in various sports. The current study examined whether acceleration performance is limited by strength, more specifically the peak limb force generation. We tested this idea by altering the mechanical demand for the supporting limb, and then determining if the peak limb force is constantly operating at its maximum level across conditions. Thirteen athletes performed maximum-effort sprint acceleration with and without an additional mass equivalent to 17 % of their body mass. We found the athletes were capable of generating a greater limb force when sprinting with the mass compared to the control. This observation suggests that acceleration performance might not be limited by the ultimate magnitude of limb force generation. It remains puzzling why the athletes would not fully utilize their limb force for propulsion. Future studies are needed to further explore other potential limiting factors for acceleration performance, such as kinematic constraints for body lean.